2014
DOI: 10.5812/aapm.17206
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Impact of Intraperitoneal Hydrocortisone With Bupivacaine on Postoperative Pain After Laparoscopic Cholecystectomy

Abstract: Background:Postoperative pain is a major complaint following laparoscopic cholecystectomy.Objectives:The aim of this study was to compare the impact of intraperitoneal hydrocortisone with intraperitoneal bupivacaine on pain relief after laparoscopic cholecystectomyPatients and Methods:In a double blind clinical trial, 63 candidates for laparoscopic cholecystectomy were randomly allocated to receive intraperitoneal instillation of either 100 mg bupivacaine in 250 mL normal saline (n = 32) or 100 mg hydrocortiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…studied the analgesic effect of intraperitoneal injection of hydrocortisone alone prior to gas insufflation in laparoscopic cholecystectomy, and they found that intraperitoneal hydrocortisone can decrease postoperative pain without postoperative complications, which is in parallel to the results of the current study. [ 16 ] Furthermore, our results agreed with Asgari et al . who studied the additive effect of intraperitoneal hydrocortisone and bupivacaine on postoperative pain in gynecological surgery, and they found that hydrocortisone with bupivacaine has a greater analgesic effect than bupivacaine only.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…studied the analgesic effect of intraperitoneal injection of hydrocortisone alone prior to gas insufflation in laparoscopic cholecystectomy, and they found that intraperitoneal hydrocortisone can decrease postoperative pain without postoperative complications, which is in parallel to the results of the current study. [ 16 ] Furthermore, our results agreed with Asgari et al . who studied the additive effect of intraperitoneal hydrocortisone and bupivacaine on postoperative pain in gynecological surgery, and they found that hydrocortisone with bupivacaine has a greater analgesic effect than bupivacaine only.…”
Section: Discussionsupporting
confidence: 93%
“…who studied hydrocortisone versus bupivacaine; this difference may be explained by the use of drug combination in our study instead of hydrocortisone alone in the previous study. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…The patients were similar regarding postoperative analgesic requirements, return of bowel function, nausea, and vomiting. [ 17 ] In a similar study, Zahra Asgari et al . studied the effect of dexamethasone added to intra-peritoneal bupivacaine on postoperative pain after gynaecological surgery and concluded that combination to be more effective than bupivacaine alone.…”
Section: Discussionmentioning
confidence: 87%
“…Sarvestani et al determined the amount of pneumoperitoneum that was still present 24 hours after LC by using chest X-rays in their calculation. [10] Several further randomised studies revealed that the operating periods of SPCP and LPCP LC were comparable. According to a meta-analysis, LPCP LC surgery takes two minutes longer than SPCP.…”
Section: Discussionmentioning
confidence: 98%